Antiproliferative Properties of Newly Synthesized 19-Nortestosterone Analogs Without Substantial Androgenic Activity - Gyovai, András; Minorics, Renáta; Kiss, Anita; Mernyák, Erzsébet; Schneider, Gyula; Szekeres, András; Kerekes, Erika; Ocsovszki, Imre; Zupkó, István (Frontiers in Pharmacology, 2018)
19-Nortestosterone C-17 epimers with prominent antiproliferative properties have been previously described. In our present study five novel 17α-19-nortestosterones (3–7) were synthesized to increase their beneficial biological activities with no associated undesired hormonal effects. The compounds were screened by a viability assay against a panel of human adherent gynecological cancer cell lines. Three of the tested derivatives (3, 4 and 5) exhibited a remarkable inhibitory effect on the proliferation of HeLa cells with IC50 values lower than that of our reference agent cisplatin (CIS). These three active agents also displayed considerable cancer selectivity as evidenced by their weaker growth inhibitory effect on non-cancerous fibroblast cells compared to CIS. The most potent newly synthesized 17α-chloro derivative (3) was selected for additional experiments in order to characterize its mechanism of action. Since nandrolone (19-nortestosterone, 1) is a structural analog with selective antiproliferative action on cervical carcinoma cells, it was utilized as a positive control in these studies. A lactate dehydrogenase (LDH) assay demonstrated a moderate cytotoxic effect of the test compounds. Cell cycle disturbance and the elevation of the hypodiploid population elicited by the test agents were detected by flow cytometry following propidium staining. The proapoptotic effects of the tested steroids were confirmed by fluorescent microscopy and a caspase-3 activity assay. Treatment-related caspase-9 activation without a substantial change in caspase-8 activity indicates the induction of the intrinsic apoptotic pathway. The selected agents directly influence the rate of tubulin assembly as evidenced by a polymerization assay. Yeast-based reporter gene assay revealed that the androgenic activity of the novel 19-nortestosterone derivative 3 is by multiple orders of magnitude weaker than that of the reference agent 1. Based on the behavior of the examined compounds it can be concluded that a halogen substitution of the 19-nortestosterone scaffold at the 17α position may produce compounds with unique biological activities. The results of the present study support that structurally modified steroids with negligible hormonal activity are a promising basis for the research and development of novel anticancer agents.